(untitled) (Patrimônio e Memória, 2015)
This article has the purpose to reflect about the life and work of Bernardo Taveira Junior (1836-1892) to understand the historical context that the writer lived in Pelotas, and the main contributions for sulina literature and Pelotas’s culture.